1992
DOI: 10.1901/jaba.1992.25-153
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Student and Teacher Responses in Observed and Generalized Settings as a Function of Supervisor Observations

Abstract: Two studies are reported in which the effects of supervisor observations of teachers' performance rate and accuracy on both teachers' and severely handicapped students' behaviors were compared with baseline supervisor observations that did not specify rate and accuracy feedback. The latter observation procedure (nonspecific feedback) was more typical of the existing practices of school supervisors. The dependent variables for the teachers were rate and accuracy of teacher behaviors to student responses in indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
112
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 16 publications
(18 reference statements)
3
112
0
Order By: Relevance
“…The presence of all of these components in instructional trials, as in the frame, meets the requirements for what has been identified in several experiments as learn units. Learn units consist of instructional presentations that have all of the tested components, described above, that were found to ensure mastery (Albers & Greer, 1991;Emurian, 2004;Emurian, Hu, Wang, & Durham, 2000;Greer, 1994;Greer & McDonough, 1999;Ingham & Greer, 1992;Selinske et al, 1992;Skinner, 1968).…”
Section: Instructional Components Of Multiple Exemplar Instructionmentioning
confidence: 99%
“…The presence of all of these components in instructional trials, as in the frame, meets the requirements for what has been identified in several experiments as learn units. Learn units consist of instructional presentations that have all of the tested components, described above, that were found to ensure mastery (Albers & Greer, 1991;Emurian, 2004;Emurian, Hu, Wang, & Durham, 2000;Greer, 1994;Greer & McDonough, 1999;Ingham & Greer, 1992;Selinske et al, 1992;Skinner, 1968).…”
Section: Instructional Components Of Multiple Exemplar Instructionmentioning
confidence: 99%
“…Interobserver agreement for the dependent variables and instructional responses, as well as procedural reliability, were calculated by the teacher's correct presentation of learn units as recorded on the Teacher Performance Rate Accuracy (Ingham & Greer, 1992) form. Interobserver agreement was assessed by having two observers simultaneously, and independently, collect data on the students' responses and the second observer record procedural reliability.…”
Section: Data Collectionmentioning
confidence: 99%
“…In a series of experiments designed to test the components of tutoring that lead to learning on the part of the tutor (Greer et al, 2004), Greer et al experimentally tested for the presence or absence of operants for the tutors prior to the tutors engaging in peer tutoring. In these studies, the tutors used learn-unit presentations (Albers & Greer, 1991;Bahadourian, Tam, Greer, & Rosseau, 2006;Emurian, 2004;Emurian, Hu, Wang, & Durham, 2000;Greer, 1994aGreer, ,1994bGreer, , 2002Greer & McDonough, 1999;Ingham & Greer, 1992) to tutor peers. Learn units are instructional presentations that include components of instruction that are deemed necessary, if not sufficient, conditions for learning (Greer, 1994a).…”
mentioning
confidence: 99%
“…That is, in the studies comparing percentage mastery versus fast rate mastery, inevitably the participants who received rate instruction also received more instructional presentations. Recently, investigators have isolated the instructional unit that predicts learning, the learn unit (Albers & Greer, 1991 ;Emurian, Hu, Wang , & Durham , 2000;Emu rian , 2004;Greer & McDonough, 1999;Greer, McCorkle, & Williams, 1989;Ingham & Greer, 1992;Selinske, Greer, & Lodhi , 1991). A learn unit includes the teacher or automated teaching device ensuring the student's attention, the unambiguous delivery of an antecedent that is to be the discriminative stimulus when the student has mastered the discriminated operant, and delivery of either a reinforcer or a correction .…”
mentioning
confidence: 99%